Local government implementation of health sector minimum standards policy: a stakeholder analysis - Arrohmah, Munib; Suryoputro, Antono; Budiyono (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to analyze the roles and positions of stakeholders in health-sector minimum service standards policy implementation (HS-MSSPI) in Wonosobo based on stakeholders' interests, authority, attitudes, influence, and involvement. Methods: This research is a descriptive qualitative study. The stages in this research are stakeholder identification, data collection through in-depth interviews, data analysis based on the stakeholder classifi- cation approach and stakeholder mapping theory. Results: The results of stakeholder classification show that decision-makers consist of the Regency Legislative Council, Regency Secretariat, Agency for Regional Development, and Health Office. Providers comprise the Health Office, Public Health Center, and Health Cadres, while Representatives comprise the Sub-District Govern- ment, Village Government, and Family Welfare Guidance (PKK) Cadres. Stakeholder mapping results show that there are two types of positions in the decision-maker category: savior and time bomb. In the provider category, there are three positions - savior, friend, and sleeping giant. At the same time, all representatives are in the friend position. Conclusion: It appears that stakeholders involved in the implementation of the HS-MSSPI in Wonosobo have not utilized their full authority to provide support and involvement. Perhaps there is room for improvement in terms of stakeholder engagement and collaboration to ensure the program's success.